Job search as a determinant of graduate over-education: Evidence from Australia - David Carroll; Massimiliano Tani (Institute for the Study of Labor (IZA), 2013)
This study considers the relationship between job search and over-education amongst recent Australian bachelor degree graduates. Using a panel estimation method, we find that using universities' career offices is associated with a reduced probability of over-education (between 3% and 8%) vis-à-vis responding to a job advertisement or searching through networking. These results are robust to alternative specifications and estimation techniques. As over-education is characterised by high persistence, the role of university career services and fairs in screening and matching the skills of graduands with the needs of employers at the entry point into the labour market cannot be overlooked.
Keywords: A22; I23; J24; 330; over-education; graduate labour market; job search